A Delphi study for setting up tobacco research and practice network in India. Issue 1 (December 2016) - Persai, Divya; Panda, Rajmohan; Kumar, Ravi; Mc.Ewen, Andy
Abstract Background There are key gaps in the production and dissemination of evidence-based tobacco control research in developing countries. In India, limited research has been made to address and understand the function, constitution, thematic areas of research of a research and practice network in tobacco control. This study aimed to identify priority areas that were agreed by stakeholders for building tobacco research and practice network in India. Methods This study used the well-established Delphi survey, which involves asking experts a recurring progression of questions through a series of questionnaires. The study was conducted in two rounds in the year 2013–14. Experts working in tobacco control participated in the study. In Round II, respondents rated agreement using a five-point Likert scale. Interquartile Range (IQR) was used to calculate the strength of the consensus. Results Experts expressed strong consensus on tobacco cessation and economic research as a focus areas for tobacco research network in India. Lack of funding was stated as a barrier impeding formation of tobacco research network in India by majority of respondents. A strong consensus was achieved on the fact that network can be sustained financially by Government funds (IQR = 1). Information sharing and capacity building of young researchers were the two major benefits as stated by respondents which achieved strong consensus. Conclusions This study produced the first national stakeholder-informed priority area for developing tobacco research and practice network in India. The consensus priorities highlight the most important and urgent needs in developing research and practice network in tobacco control.